PENTINGNYA PENDIDIKAN MENGAJI PADA ANAK KELAS 5 DAN 6 DI SDN 27 LADANG HUTAN: KENDALA DAN SOLUSINYA - Dzakiyya Shafarlin; M. Isnando Tamrin; Nelfanita Nelfanita (ADIBA : JOURNAL OF EDUCATION, 2024)
Al-Qur'an education plays a central role in forming the character, morals and spirituality of grade 5 and 6 children at SDN 27 Ladang Hutan. In this context, this research uses a qualitative approach to gain a holistic understanding of the implementation of Al-Qur'an education. The research subjects involved teachers and students in grades 5 and 6, with data collection techniques involving observation and interviews. The research results show that teaching the Al-Qur'an has a positive impact on increasing religious knowledge, building character, developing Arabic language skills, and increasing children's concentration and discipline. However, obstacles such as the lack of availability of qualified Koran teachers, a curriculum that is not integrated, and a lack of facilities and infrastructure are obstacles in implementing Al-Qur'an education. The proposed solutions include increasing teacher training, curriculum integration, improving facilities and infrastructure, and involving parents in supporting education at home. By implementing these solutions, it is hoped that Al-Qur'an education can be implemented more effectively at SDN 27 Ladang Hutan, providing great benefits in shaping the character and morals of children at the elementary school level.